Simultaneous electropolymerization/Au nanoparticle generation at an electrified liquid/liquid micro-interface. (10th September 2022) - Moshrefi, Reza; P． Connors, Evan; Merschrod, Erika; Stockmann, T. Jane
Highlights: Simultaneous Au nanoparticle generation and terthiophene electropolymerization. Nanocomposite film formation at an electrified liquid/liquid interface. Asymmetric nanoparticle generation and electropolymerization. Abstract: Free-standing nanocomposite thin-films for bioimplantation and (electro)catalysis are still an immature field despite the need for new materials. Herein, the micro liquid|liquid interface between water|1, 2-dichloroethane (w|DCE) positioned at the tip of a pulled pipette has been exploited to generate a free-standing thin-film incorporating Au NPs electrogenerated in situ by reduction of a gold salt in the aqueous phase and using 2, 2′:5′, 2″-terthiophene (TT) as monomer/electron donor dissolved in the DCE phase. Low pH of the aqueous phase generated incomplete, poorly formed films, as evidenced by TEM and AFM images of the final film. At high pH the half-wave potential of the electron transfer wave shifted to lower potentials (∼0.35 V versus simple ion transfer of AuCl4 – ) with repeated cyclic voltammetric cycling indicating improved thermodynamics. Imaging of films produced at pH's >5.5 were robust. These results indicate the need of a Brønsted base to capture protons and facilitate TT +, radical cation coupling. TEM and AFM imaging are complemented by in situ impedance spectroscopy measurements that show an increase in the capacitive nature of the interface as [TT] and pH increases along with increased cycling of the potential. Curve fitting using equivalent circuit models required the addition of a second capacitator element to mimic the generation of a porous film at the liquid|liquid interface, i.e., a liquid|solid|liquid interface. By reducing the required overpotential, one can prevent overoxidation of the monomer/polymer. AFM measurements of formed thin-films mechanically deposited onto silicon substrates were found to be ∼0.4 μm in thickness with Au NP radius increasing concomitantly with distance away from the w|DCE interface. Graphic abstract: Image, graphical abstract